Kingfisher child's world encyclopedia vol. 1: the universe - Grabham Sue (Kingfisher London, 1994)
A guide to the questions pre-schoolers ask. It covers the universe, our planet earth, the sea, all kinds of animals, plants, when dinosaurs lived, my body, machines, science, people and places.